2019
DOI: 10.1093/conphys/coz073
|View full text |Cite
|
Sign up to set email alerts
|

Thermal physiology and activity in relation to reproductive status and sex in a free-ranging semelparous marsupial

Abstract: In a changing climate, southern hemisphere mammals are predicted to face rising temperatures and aridity, resulting in food and water shortages, which may further challenge already constrained energetic demands. Especially semelparous mammals may be threatened because survival of the entire population depends on the success of a single breeding event. One of these species, the yellow-footed antechinus, Antechinus flavipes, a small, heterothermic marsupial mammal, commences reproduction during winter, when inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Extensive reviews on Bergmann's rule have found mixed support for temperature being the main factor influencing body size in mammals, and have suggested that other factors such as food availability are more important (Alhajeri and Steppan, 2016;Gohli and Voje, 2016). As antechinus are known to increase torpor use when exposed to cold conditions to save energy (Geiser, 1988;Parker et al, 2019), it is likely that they increased torpor use when exposed to the cold treatment. Therefore, this strategy, along with changes in activity patterns, may reduce body mass loss under cold conditions and explain why there was no difference between the treatment groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive reviews on Bergmann's rule have found mixed support for temperature being the main factor influencing body size in mammals, and have suggested that other factors such as food availability are more important (Alhajeri and Steppan, 2016;Gohli and Voje, 2016). As antechinus are known to increase torpor use when exposed to cold conditions to save energy (Geiser, 1988;Parker et al, 2019), it is likely that they increased torpor use when exposed to the cold treatment. Therefore, this strategy, along with changes in activity patterns, may reduce body mass loss under cold conditions and explain why there was no difference between the treatment groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Food withdrawal increased daily torpor expression to about 30-80% from autumn to spring when juveniles are excluded, which did express torpor in summer (Geiser, 1988). In the field, A. flavipes expressed torpor in winter, but torpor patterns were strongly affected by reproductive status (Parker et al, 2019), whereas in A. stuartii, daily torpor in winter was mainly affected by weather (Hume et al, 2020).…”
Section: Marsupialsmentioning
confidence: 92%
“…Andean Hillstar, Oreotrochilus estella, spring and autumn unknown (Carpenter, 1974) Rufous hummingbird, Selasphorus rufus, migratory, winter unknown (Hiebert, 1993) Sunbird, Nectarina famosa, summer (Downs and Brown, 2002) Black-capped chickadee, Poecile atricapilla, spring and autumn unknown (Sharbaugh, 2001) Fat-tailed dunnart, Sminthopsis crassicaudata (Geiser and Baudinette, 1987;Warnecke et al, 2008) Stripe-faced dunnart, Sminthopsis macroura (Geiser and Baudinette, 1987;Körtner and Geiser, 2009) Kowari, Dasyuroides byrnei (Geiser and Baudinette, 1987) Blossom-bat, Syconycteris australis (Geiser et al, 1996;Coburn and Geiser, 1998) Elephant shrew, Elephantulus myurus (Mzilikazi and Lovegrove, 2004) White-footed mouse, Peromyscus leucopus (Lynch et al, 1978) Deer mouse, Peromyscus maniculatus (Tannenbaum and Pivorun, 1989) Desert hamster, Phodopus roborovskii (Chi et al, 2016;Geiser et al, 2019) Spiny mouse, Acomys russatus (Levy et al, 2011) Autumn to spring Tawny frogmouth, Podargus strigoides (Körtner et al, 2001) Owlet-nightjar, Aegotheles cristatus (Brigham et al, 2000) Whip-poorwill, Caprimulgus vociferous, migratory, winter unknown (Lane et al, 2004) Noisy miner, Manorina melanocephala (Geiser, 2019) Brown antechinus, Antechinus stuartii (Geiser, 1988;Hume et al, 2020) Yellow-footed antechinus, Antechinus flavipes (Geiser, 1988;Parker et al, 2019) Sugar glider, Petaurus breviceps (Körtner and Geiser, 2000a;Nowack et al, 2015) Djungarian hamster, Phodopus sungorus (Heldmaier and Steinlechner, 1981) other aspect of seasonal torpor use, the control of its expression differs among species and revealing the responsible cues will require further work.…”
Section: All Yearmentioning
confidence: 99%
“…No other animals (six males and four females) entered torpor with all other animals maintaining a T b between 29.9°C and 39.8°C (Stannard et al, unpublished). Torpor has been used by other semelparous dasyurid marsupials more frequently after wildfires, during pregnancy and to avoid unfavorable weather conditions (Hume et al, 2020; Matthews et al, 2017; Parker et al, 2019). Thus torpor is important for survival as an energy saving mechanism, and additionally using torpor allows them to avoid predators.…”
Section: Red‐tailed Phascogalesmentioning
confidence: 99%